(untitled) (Research, Society and Development, 2023)
Objective: to report the creation and implementation of preventive actions to reduce falls in an inpatient unit of a private hospital in the state of Rio de Janeiro. Method: this is an experience report on the implementation of reduction and prevention of falls in patient rooms using Lean Healthcare methodology. Results: the creation of a team and a visual panel for a multidisciplinary team based on the Lean Healthcare methodology made it possible to identify the most critical patients for falls and reduced the risks by 30% in the current year and 0% of falls of companions. In addition, this strategy made it possible to remind companions of the need to ask for help in mobilizing bedridden patients. Final considerations: using the Lean Healthcare methodology in the prevention of falls was effective in the actions developed, improving the quality of care, allowing to intervene effectively and enhance patient safety.